Molecular characterization of extended-spectrum cephalosporin and fluoroquinolone resistance genes in Salmonella and Shigella isolated from clinical specimens in Thailand. Issue 12 (December 2022) - Sriyapai, Thayat; Pulsrikarn, Chaiwat; Chansiri, Kosum; Sriyapai, Pichapak
Abstract: Antimicrobial resistance of Salmonella and Shigella has become a major clinical and public health problem. The incident of co-resistance to third generation cephalosporins and fluoroquinolone is a serious therapeutic issue in Thailand. The present study aimed to investigate the antimicrobial resistance and molecular character of clinical Shigella and Salmonella isolates. A total of 33 Salmonella and 53 Shigella cefotaxime-resistant isolates were collected from human clinical cases in Thailand during the period from 2011–2018. The antimicrobial susceptibility of Salmonella and Shigella was determined by the disk diffusion method, and extended-spectrum beta-lactamase (ESBL) production was characterized by the double-disk synergy test. Genotype characterization was performed by PCR and DNA sequencing. Thirty-two (97.0%) and fifty-two (98.1%) isolates of cefotaxime-resistant Salmonella and Shigella, respectively, were identified as ESBL producers. Shigella sonnei (4 isolates), Salmonella serovar 4, 5, 12:i:- (6 isolates), Salmonella serovar Agona (2 isolates) and Salmonella serovar Rissen (2 isolates) showed co-resistance to ciprofloxacin and cefotaxime or ceftriaxone. The combination of bla CTX-M-15 plus other ESBL and/or AmpC β-lactamase genes was the most dominant of the genotype patterns in ESBL-producing isolates. The plasmid harbouring the aac(6′)-Ib-cr gene and mutations of gyrA (S83F, D87Y or D87G) and parC (T57S) genes was found in 2 ESBL-producing Salmonella isolates. Three Shigella sonnei isolates harboured mutations in gyrA (S83L, D87Y or D87G), and only one Shigella sonnei phase I isolate showed mutations in both gyrA (S83L and D87G) and parC (S80I) genes. Among these clinical Shigella sonnei isolates, qnrS determinants were identified. Production of ESBLs is an important mechanism for resistance to extended-spectrum cephalosporins in Salmonella and Shigella . The emergence of a decreased susceptibility to extended-spectrum cephalosporins and fluoroquinolone in ESBL-producing isolates has important clinical and therapeutic implications. Abstract : Antimicrobial resistance; Extended-spectrum cephalosporins; Salmonella ; Shigella ; Quinolones.